A light-weight high-strength shoe sole material and a method for preparing the same

CN123004072APending Publication Date: 2026-10-30ZHONGSHAN ZHANTU SHOE MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510556072.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但往往发泡的轻质材料不具备较高的强度,大多应用在鞋中底领域

Benefits of technology

[0037](1)本发明提供的轻质高强度鞋底材料具有轻质化、高强度、高耐磨性等多种特性,可用于制备轻质化薄底鞋材。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005383437040000061
    Figure BDA0005383437040000061
Patent Text Reader

Abstract

The present application relates to the technical field of rubber modification in shoe materials, and particularly relates to a light-weight high-strength shoe sole material and a preparation method thereof. The present application uses polyolefin block copolymer, styrene thermoplastic elastomer and ethylene-vinyl acetate copolymer as a rubber matrix, ensures the performance balance of wear resistance, elasticity and flexibility, and introduces light-weight fillers to reduce weight and simultaneously perform reinforcement so as to have high strength, and finally compounding to obtain a light-weight high-strength shoe sole material. The light-weight high-strength shoe sole material provided by the present application has multiple characteristics such as light weight, high strength and high wear resistance, and can be used for preparing light-weight thin sole shoe materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of rubber and plastic material modification technology in footwear, specifically to a lightweight, high-strength shoe sole material and its preparation method. Background Technology

[0002] Currently, with increasing health awareness and changing lifestyles, people's demand for lightweight shoes is growing. The fast pace of modern urban life leads people to seek more convenient and comfortable wearing experiences, especially for daily commutes, leisure activities, and fitness exercises. Lightweight, flexible, and portable shoes are becoming the first choice for more and more consumers.

[0003] Ethylene-vinyl acetate copolymer (EVA) foam materials are lightweight, shock-absorbing, and resilient, making them widely used in athletic shoe soles. For example, patent CN114773658A discloses a high-softness, elastic shock-absorbing EVA foam sole material, its preparation method, and its applications, utilizing EVA foaming technology to achieve a lightweight effect. However, lightweight foamed materials often lack high strength and are mostly used in shoe midsoles.

[0004] In the field of thin-soled footwear materials, there is also a high demand for lightweighting; however, as thin-soled footwear materials, due to the thinner sole, the requirements for strength and abrasion resistance are higher, and simple EVA foaming cannot meet the application needs of the field of thin-soled footwear materials.

[0005] Therefore, it is necessary to develop a synthetic rubber material that can meet the requirements of lightweight while also possessing the strength and abrasion resistance needed for thin-soled shoe materials. Summary of the Invention

[0006] This invention provides a lightweight, high-strength shoe sole material and its preparation method. The lightweight, high-strength shoe sole material provided by this invention, while possessing lightweight characteristics, ensures that the shoe material has certain strength and abrasion resistance, making it more suitable for use as a thin-soled shoe material.

[0007] To achieve the above objectives, the present invention provides the following technical solution:

[0008] This invention provides a lightweight, high-strength shoe sole material, comprising, by weight:

[0009] Polyolefin block copolymer: 20-30 parts

[0010] Styrene-based thermoplastic elastomers: 30-40 parts,

[0011] Ethylene-vinyl acetate copolymer: 20-30 parts

[0012] Compatibilizer: 5-10 parts

[0013] Antioxidant: 0.1–2 parts,

[0014] Lightweight filler: 10-30 parts.

[0015] This application uses polyolefin block copolymers, styrene thermoplastic elastomers, and ethylene-vinyl acetate copolymers as rubber matrices, ensuring a balance of wear resistance, elasticity, and flexibility. Lightweight fillers are introduced to reduce weight while providing reinforcement to give it high strength, ultimately resulting in a lightweight and high-strength shoe sole material.

[0016] Among them, polyolefin block copolymers have good softness and elasticity, providing good comfort; styrene-based thermoplastic elastomers have good abrasion resistance, ensuring the service life of thin-soled shoe materials; and ethylene-vinyl acetate copolymers, as lightweight and high-strength materials, have low density, effectively reducing the weight of shoe sole materials. Therefore, using styrene-based thermoplastic elastomers to provide high strength and abrasion resistance, and using polyolefin block copolymers and ethylene-vinyl acetate copolymers to provide flexibility and elasticity, can yield a rubber matrix with certain strength, abrasion resistance, and elasticity.

[0017] Based on the above, lightweight fillers are introduced to reinforce and further enhance the strength of the rubber matrix, ultimately resulting in lightweight, high-strength, and highly wear-resistant shoe materials.

[0018] The specific amounts of the special raw materials in this application support and complement each other in function, which can improve the overall performance of lightweight and high-strength shoe sole materials.

[0019] Preferably, the compatibilizer includes at least a maleic anhydride-grafted compatibilizer.

[0020] More preferably, the maleic anhydride graft compatibilizer is one or more of maleic anhydride-grafted SBS, maleic anhydride-grafted SEBS, maleic anhydride-grafted EPDM, maleic anhydride-grafted PP, maleic anhydride-grafted POE, and maleic anhydride-grafted TPE.

[0021] More preferably, the compatibilizer is maleic anhydride-grafted SBS.

[0022] Compatibilizers can help blend polyolefin block copolymers, styrene thermoplastic elastomers, ethylene-vinyl acetate copolymers, and lightweight fillers.

[0023] Preferably, the vinyl acetate content of the ethylene-vinyl acetate copolymer is 20-25 wt%.

[0024] Preferably, the polyolefin block copolymer is an ethylene-octene copolymer.

[0025] Preferably, the styrene-based thermoplastic elastomer is one or more of styrene-butadiene-styrene block copolymer, hydrogenated styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, or hydrogenated styrene-isoprene-styrene block copolymer.

[0026] Preferably, the lightweight filler is silica and hollow glass microspheres, wherein the average particle size of the silica is 50-300 nm and the average particle size of the hollow glass microspheres is 10-30 μm.

[0027] The density of hollow glass microspheres is between 0.1 and 0.7 g / mL, which is much lower than that of traditional fillers (such as calcium carbonate and talc). In addition, the hollow structure of hollow glass microspheres can reduce weight while providing a certain degree of rigidity, making them less prone to deformation under pressure.

[0028] Small-particle-size nano-sized silica is more easily and uniformly dispersed in the rubber matrix, reducing agglomeration; while large-particle-size micron-sized hollow glass microspheres can provide rigidity. Mixing the two yields a nano-micron system filler structure, which not only reinforces the rubber matrix but also prevents particle agglomeration that could lead to stress concentration and uneven stress distribution in the resulting shoe sole, causing cracking.

[0029] Preferably, the mass ratio of the silica to the hollow glass microspheres is (0.8-1.5):1.

[0030] More preferably, the mass ratio of the silica to the hollow glass microspheres is (0.8–1.2):1.

[0031] More preferably, the mass ratio of the silica to the hollow glass microspheres is (0.8-1.0):1.

[0032] More preferably, the mass ratio of the silica to the hollow glass microspheres is 1:1.

[0033] Preferably, the antioxidant is one or more of antioxidant 1010, antioxidant 168 and antioxidant 1076.

[0034] Preferably, it also includes 0 to 3 parts lubricant, 0 to 2 parts plasticizer and 0 to 3 parts colorant.

[0035] This invention also provides a method for preparing a lightweight, high-strength shoe sole material, characterized by comprising: weighing and mixing polyolefin block copolymer, styrene thermoplastic elastomer, ethylene-vinyl acetate copolymer, compatibilizer, antioxidant and inorganic filler, followed by extrusion pelletizing and air cooling to obtain composite material A; melting and mixing composite material A, followed by extrusion, sheeting, cooling, cutting and roughening to obtain a synthetic rubber material for thin-soled shoe materials.

[0036] Therefore, the present invention has the following beneficial effects:

[0037] (1) The lightweight and high-strength shoe sole material provided by the present invention has multiple characteristics such as lightweight, high strength and high wear resistance, and can be used to prepare lightweight thin-soled shoe materials.

[0038] (2) The lightweight and high-strength shoe sole material provided by the present invention uses polyolefin block copolymer, styrene thermoplastic elastomer and ethylene-vinyl acetate copolymer as rubber matrix, which ensures the balance of wear resistance, elasticity and flexibility, and introduces lightweight filler to reduce weight and reinforce it to make it have high strength.

[0039] (3) The lightweight and high-strength shoe sole material provided by the present invention uses lightweight hollow glass microspheres as micron-level materials to construct a nano-micron-level filler system to obtain a high-strength lightweight and high-strength shoe sole material. Detailed Implementation

[0040] The present invention will be further described below with reference to specific embodiments. Those skilled in the art will be able to implement the present invention based on these descriptions. Furthermore, the embodiments of the present invention described below are generally only some, not all, of the embodiments of the present invention. Therefore, all other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort should fall within the scope of protection of the present invention.

[0041]

Example

[0042] The raw materials used in this section are: SBS3546, thermoplastic styrene-butadiene rubber, a styrene-butadiene-styrene block copolymer, purchased from Dongguan Suwei New Materials Co., Ltd.; POE, polyolefin elastomer, ethylene-octene copolymer, Dow Chemical ENGAGE 8480, purchased from Dongguan Shuo Plastic Raw Materials Co., Ltd.; EVA, ethylene-vinyl acetate copolymer, VA910, Lotte Chemicals, South Korea, VA content 21.5wt%, purchased from Shanghai Huihang New Materials Co., Ltd.; and silica, A200, Degussa, fumed silica. Silica, particle size less than 0.3μm, purchased from Hubei Chengfeng Chemical Co., Ltd.; maleic anhydride grafted SBS, CAS112-84-5, purchased from Dongguan Bailing New Materials Co., Ltd.; antioxidant 1010, pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyphenylpropionate), purity 98%, purchased from Shanghai Yuanye Biotechnology Co., Ltd.; antioxidant 168, phenyl tris(2,4-di-tert-butyl)phosphite, purity 98%, purchased from Shanghai Yuanye Biotechnology Co., Ltd.; hollow glass microspheres, CAS 7631-86-9, CK45 (10~30μm), purity 99.5%, purchased from Guangzhou Shenna Trading Co., Ltd.; silica, ML-SiO2-W10 (10μm), purity 99.9%, purchased from Zhejiang Manli Nanotechnology Co., Ltd.; TPU, thermoplastic polyurethane, Dow 202EZ, purchased from Dongguan Nabaichuan Plastics Co., Ltd.

[0043] Example 1

[0044] The formula, by weight, is as follows: 23 parts POE, 35 parts SBS3546, 25 parts EVA, 5 parts maleic anhydride-grafted SBS, 6 parts A200 silica (less than 300nm), 5 parts hollow glass microspheres (10-30μm), 0.5 parts antioxidant 1010, and 0.5 parts antioxidant 168.

[0045] When the internal mixer reaches 90℃, open the internal mixer and add all the raw materials according to the above formula. Mix them into a dough, then flip it over and continue internal mixing under pressure until the mixing temperature reaches 120℃. Add the mixed material to the forced feed granulator and set the forced feed granulator temperature as follows: 90℃ for the first stage, 110℃ for the second stage, 100℃ for the third stage, and 140℃-150℃ for the fourth stage. Extrude and pelletize the pellets, then let them pass through two stages of air cooling before flowing into a vibrating screen to further disperse and cool the pellets. Finally, bag and seal the pellets.

[0046] The mixed granules obtained above are added to an extrusion machine (i.e., the sleeve outside the screw has vent holes to remove moisture from the rubber compound). The material passes through a die to form sheets, which are then rolled by a die to obtain sheets of the required thickness. These sheets are then pulled out by a traction machine and cut to the required length by an automatic cutting machine. After being arranged, they are allowed to cool naturally. The cooled sheets are then placed into a cutting machine and cut into thin-sole materials of the required shape using a die. The cut thin soles are then placed into an automatic roughening machine to roughen both sides, obtaining the final thin-sole shoe material.

[0047] Comparative Example 1 (POE only)

[0048] This comparative example is basically the same as Example 1, except that:

[0049] By weight, weigh out 83 parts POE, 5 parts maleic anhydride-grafted SBS, 6 parts A200 silica (less than 300nm), 5 parts hollow glass microspheres (10-30μm), 0.5 parts antioxidant 1010, and 0.5 parts antioxidant 168.

[0050] Comparative Example 2 (SBS only)

[0051] This comparative example is basically the same as Example 1, except that:

[0052] By weight, weigh out 83 parts SBS3546, 5 parts maleic anhydride-grafted SBS, 6 parts A200 silica (less than 300 nm), 5 parts hollow glass microspheres (10-30 μm), 0.5 parts antioxidant 1010, and 0.5 parts antioxidant 168.

[0053] Comparative Example 3 (EVA only)

[0054] This comparative example is basically the same as Example 1, except that:

[0055] By weight, weigh out 83 parts EVA, 5 parts maleic anhydride-grafted SBS, 6 parts A200 silica (less than 300nm), 5 parts hollow glass microspheres (10-30μm), 0.5 parts antioxidant 1010, and 0.5 parts antioxidant 168.

[0056] Comparative Example 4 (TPU replacing POE)

[0057] This comparative example is basically the same as Example 1, except that:

[0058] The following formula is weighed by weight: 23 parts TPU, 35 parts SBS3546, 25 parts EVA, 5 parts maleic anhydride-grafted SBS, 6 parts A200 silica (less than 300nm), 5 parts hollow glass microspheres (10-30μm), 0.5 parts antioxidant 1010, and 0.5 parts antioxidant 168.

[0059] Comparative Example 5 (TPU replaces SBS)

[0060] This comparative example is basically the same as Example 1, except that:

[0061] The formula, by weight, is as follows: 23 parts POE, 35 parts TPU, 25 parts EVA, 5 parts maleic anhydride-grafted SBS, 6 parts A200 silica (less than 300nm), 5 parts hollow glass microspheres (10-30μm), 0.5 parts antioxidant 1010, and 0.5 parts antioxidant 168.

[0062] Comparative Example 6

[0063] This comparative example is basically the same as Example 1, except that:

[0064] The formula, by weight, is as follows: 23 parts POE, 35 parts SBS3546, 25 parts EVA, 5 parts maleic anhydride-grafted SBS, 4 parts A200 silica (less than 300nm), 7 parts hollow glass microspheres (10-30μm), 0.5 parts antioxidant 1010, and 0.5 parts antioxidant 168.

[0065] Comparative Example 7

[0066] This comparative example is basically the same as Example 1, except that:

[0067] The formula, by weight, is as follows: 23 parts POE, 35 parts SBS3546, 25 parts EVA, 5 parts maleic anhydride-grafted SBS, 7 parts A200 silica (less than 300nm), 4 parts hollow glass microspheres (10-30μm), 0.5 parts antioxidant 1010, and 0.5 parts antioxidant 168.

[0068] Comparative Example 8

[0069] This comparative example is basically the same as Example 1, except that:

[0070] The formula is weighed by weight as follows: 23 parts POE, 35 parts SBS3546, 25 parts EVA, 5 parts maleic anhydride-grafted SBS, 6 parts silica (10μm), 5 parts hollow glass microspheres (10-30μm), 0.5 parts antioxidant 1010, and 0.5 parts antioxidant 168.

[0071] Comparative Example 9 (without hollow glass microspheres)

[0072] This comparative example is basically the same as Example 1, except that:

[0073] The formula is weighed by weight as follows: 23 parts POE, 35 parts SBS3546, 25 parts EVA, 5 parts maleic anhydride-grafted SBS, 11 parts A200 silica (less than 300nm), 0.5 parts antioxidant 1010, and 0.5 parts antioxidant 168.

[0074] [Performance Testing]

[0075] Table 1. Physical performance results of each embodiment / comparative example.

[0076]

[0077] Observing the data in Table 1, it can be seen that the nano- to micron-scale filler system of silica and hollow glass microspheres is the most critical for obtaining high-strength and high-wear-resistance shoe materials. When nano-scale silica is replaced with micron-scale silica, the poor dispersibility of large-particle silica results in a weak reinforcing effect, leading to a significant decrease in hardness, tensile strength, elongation at break, and tear resistance, while a significant increase in abrasion loss. In addition, TPU is considered to be a rubber matrix material with high elasticity and wear resistance, similar to SBS and POE, but in actual selection, the applicant found that its effect is not as comprehensive as that of SBS / POE / EVA.

Claims

1. A lightweight, high-strength shoe sole material, characterized in that, By weight, including: Polyolefin block copolymer: 20-30 parts Styrene-based thermoplastic elastomers: 30-40 parts, Ethylene-vinyl acetate copolymer: 20-30 parts Compatibilizer: 2-6 parts Antioxidant: 0.1–2 parts, Lightweight filler: 10-30 parts.

2. The lightweight, high-strength shoe sole material as described in claim 1, characterized in that, The compatibilizer includes at least a maleic anhydride-grafted compatibilizer.

3. The lightweight, high-strength shoe sole material as described in claim 1, characterized in that, The vinyl acetate content of the ethylene-vinyl acetate copolymer is 20-25 wt%.

4. The lightweight, high-strength shoe sole material as described in claim 1, characterized in that, The styrene-based thermoplastic elastomer is one or more of the following: styrene-butadiene-styrene block copolymer, hydrogenated styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, or hydrogenated styrene-isoprene-styrene block copolymer.

5. The lightweight, high-strength shoe sole material as described in claim 1, 3, or 4, characterized in that, The polyolefin block copolymer is an ethylene-octene copolymer.

6. The lightweight, high-strength shoe sole material as described in claim 1, characterized in that, The lightweight filler is silica and hollow glass microspheres, wherein the average particle size of the silica is 50-300 nm and the average particle size of the hollow glass microspheres is 10-30 μm.

7. The lightweight, high-strength shoe sole material as described in claim 6, characterized in that, The mass ratio of the silica to the hollow glass microspheres is (0.8–1.5):

1.

8. The lightweight, high-strength shoe sole material as described in claim 1, characterized in that, The antioxidant is one or more of antioxidant 1010, antioxidant 168 and antioxidant 1076.

9. The lightweight, high-strength shoe sole material as described in claim 1, characterized in that, It also includes 0 to 3 parts lubricant, 0 to 2 parts plasticizer and 0 to 3 parts colorant.

10. The method for preparing the lightweight, high-strength shoe sole material according to any one of claims 1 to 8, characterized in that, include: Weigh out polyolefin block copolymer, styrene thermoplastic elastomer, ethylene-vinyl acetate copolymer, compatibilizer, antioxidant and inorganic filler, mix them in an intensive mixing process, then extrude and pelletize, and air-cool to obtain composite material A; melt-mix composite material A, then extrude, press, cool, cut and roughen to obtain synthetic rubber material for thin-soled shoe materials.

Citation Information

Patent Citations

  • Wear-resistant, light and anti-slip high-softness elastic cushioning EVA (Ethylene Vinyl Acetate) foaming sole material as well as preparation method and application thereof

    CN114773658A